Assessing the Social and Economic Benefits of Organic Agriculture Conversion - Fajar Setiawan; Rizki Kharina Dewi; Hendrik Widiyanto (Jambura Equilibrium Journal, 2020)
Unsustainability of conventional agriculture practices led to the increase of conversion to organic agriculture. This study investigates farmers’ personal motive of conversion and examine the significance of conversion period in organic agriculture practice. This study further analyses social and economic benefits of conversion to organic agriculture and its contribution in increasing sustainable rural development in Indonesia. This study uses mixed method analysis by conducting qualitative and quantitative data collection strategy. This study uses purposive sampling approach and further determined Getasan Organic Agriculture as main case study. The findings suggest that farmers’ personal motive on conversion mainly revolves around environmental concerns. Furthermore, this study found that farmers considered conversion period as opportunity costs that will result in higher social and economic benefit. Lastly, this study found that organic agriculture practice is beneficial socially and economically and is expected to be more attractive in the future. Keywords: Organic agriculture, conversion period, motives on conversion, sustainable development.